Stranded cetaceans of Tacna, Peru (2002-2010) - Pizarro-Neyra, José (2010)
Stranded cetaceans in the coast of Tacna since April 2002 to January 2010 are reported in this work. The research was conducted in Tacna region, southern Perú. The fishing villages surveyed were: Los Palos, Vila-vila, Morro Sama and Ite. According with the results, the more abundant cetaceans in the strandings were: Phocoena spinipinnis (85%) and Tursiops truncatus (8%). Other identified species are Grampus griseus, Eubalaena australis and Physeter macrocephalus. The strandings of greater cetaceans were observed only in Los Palos, meanwhile, 80% of the all stranded animals were founded in Ite. The cause of stranding of some porpoises is due to the entanglement in nets of artisanal fisheries. The stranding of sperm-whale is linked with the anomalous values of superficial sea temperature.